Economics for business and management : - Griffiths, Alan (Prentice Hall / Financial Times, 2005)
This text on key principles of microeconomics and macroeconomics focuses on real-life business situations in both functional and strategic areas of business and management. Detailed consideration is given to the political, legal, ethical, sociocultural, and technological dimensions of the business environment. Learning features include objectives, checkpoints, key points, multiple-choice quizzes, data response and stimulus questions, and essay questions.